Pengaruh Penerapan Internet of Things (IoT), Good Governence dan Standar Akuntansi Pemerintah terhadap Akuntabilitas Laporan Keuangan pada Pemerintah Kota Malang Tahun 2021-2023 - Vebiola Puspa Asa Pujangga; Endah Puspitosarie; Dwi Anggarani; Indah Dewi Nurhayati (CV. ITTC INDONESIA, 2025)
This study aims to examine the influence of the implementation of the Internet of Things (IoT), principles of good governance, and the application of Government Accounting Standards (SAP) on the accountability of financial reporting in the Malang City Government during the period of 2021–2023. The research is grounded in the growing demand for more transparent, accountable, and efficient public financial management in the digital era. A quantitative approach was employed using survey methods targeting respondents directly involved in regional financial management. Data were collected through questionnaires and analyzed using multiple linear regression. The results indicate that all three independent variables, IoT, good governance, and SAP have a significant impact on the accountability of financial reports, both simultaneously and partially. These findings highlight the critical role of technological innovation, sound governance practices, and adherence to accounting standards in building reliable and accountable financial reporting systems at the local government level. This study offers both theoretical and practical implications for the advancement of public financial policy through the integration of technology and good governance principles.